Intracellular sirolimus concentration is reduced by tacrolimus in human pancreatic islets in vitro. (23rd June 2015) - Kloster‐Jensen, Kristine; Vethe, Nils Tore; Bremer, Sara; Abadpour, Shadab; Korsgren, Olle; Foss, Aksel; Bergan, Stein; Scholz, Hanne
Abstract Main problem Islet transplantation has become a promising treatment for type 1 diabetes. However, immunosuppressive drugs used today cause islet deterioration and modification strategies are necessary. But little is known about pharmacokinetics interactions and intracellular concentrations of immunosuppressive drugs in human islets. Methods We determined the pharmacokinetics of tacrolimus and sirolimus in islets by measuring intracellular concentration after exposure alone or in combination at two different doses up to 48 h. A quantification technique established in our laboratory using a Micromass Quattro micro API MS/MS‐instrument with electrospray ionization was used. Islets function was measured by oxygen consumption rates. Presence of drug transporters OATP1B1 and ABCB1 and metabolizing enzyme CYP3A4 in islets were quantified using real‐time quantitative PCR. Results Islets incubated with tacrolimus and sirolimus had a significant decrease in intracellular concentration of sirolimus compared to sirolimus alone. Reduced intracellular sirolimus concentration was followed by increased p70S6k phosphorylation suggesting preservation of the mTOR‐signaling pathway. Drug transporters OATP1B1 and ABCB1 and enzyme CYP3A4 were expressed in human islets, but were not involved in the reduced sirolimus concentration by tacrolimus. Conclusion These findings provide new knowledge of the drug interaction between tacrolimus and sirolimus, suggesting that tacrolimus has an inhibitory effect on the intracellular concentration of sirolimus in human islets.